PEMBUATAN MEDIA PEMBELAJARAN FISIKA BERBASIS MULTIMEDIA INTERAKTIF UNTUK MTS BUSTANUL ULUM PAKISAJI MENGGUNAKAN ADOBE FLASH - FIGOR AGUSYANA QOIRIAWAN, FIGOR AGUSYANA QOIRIAWAN (Jurnal Fakultas Teknologi Informasi, 2012)
ABSTRACTQoiriawan,  Figor Agusyana. 2013. Physics-Based Media Interactive Multimedia LearningTo Mts Bustanul Ulum Pakisaji Requires Adobe Flash. StudiesProgram, Faculty of Information Technology University ofMalang Kanjuruhan. Supervisor: Alex Endy  Budianto, S. Kom,MM.Keywords: Media Learning Physics-Based Interactive Multimedia.Visual media in the physical sciences in particular IPA is very minimal in  encounter.Most students get learning materials only  the  source of information from books or teachers,which  resulting in low visualization of the students on the material  which is learn.  It causesbored to the  students in studying science. Computers can be used as atool to make  theabstract concept concrete becomes  static and animated visualizations. Through animation  itcan make  more attractive concept that adds to the motivation in  learning the science. By  thepossibility of making computers as interactive multimedia programs.Therefore, in order to learn the process of science is not boring and more interesting.The  reseacher  interested  in  conducting  this thesis  under title of  "Media Physics-BasedInteractive Multimedia Learning to Mts Bustanul Ulum Pakisaji  by Using Adobe Flash".From these results,  it can be concluded that the Media Learning Physics -BasedInteractive Multimedia For Mts Bustanul Ulum Pakisaji Using Adobe Flash, can help   toclarify the  understanding  of  the nature of the material presented on the states of matter,expansion, and heat transfer, the nature of the substance, mixture separation, and chemicalreactions .